Low Phosphorus and Protein-Based Snack Bar Processed Products of Brown Rice for Sufferers Chronic Kidney Disease - Armiyani Armiyani; Susyani Susyani; Imelda Telisa (Jurnal Ilmu dan Teknologi Kesehatan, 2021)
Chronic kidney disease (CKD) causes metabolic disorders such as hyperphosphatemia. Limiting phosphorus and protein intake is one option, but egg whites and brown rice snack bars are another. This study aimed to compare CKD patients' mean blood urea levels before and after intervention at Prabumulih City Hospital in South Sumatra. This study employs a two-stage quasy design. The first stage of making snack bars was organoleptic tests with Friedman test analysis. In Phase II, patients are given snack bars, and their blood urea levels are measured using t-dependent tests. Purposive sampling was used to select CKD patients from a group of up to 13. The best formula for the brown rice snack bar was formula 3 with 225 kcal energy, 3.46 g protein, 12.68 g fat, 24.26g carbohydrate, 38.92 g phosphorus, and a Phosphorus-Protein ratio of 11.24 mg/g. The mean blood urea levels of CKD patients differed statistically (p-value 0.000). With its low protein and low phosphorus-to-protein ratio, the snack bar's formula can lower blood urea levels in CKD patients. So this snack bar can be used as CKD diet food.